A High-Level Fungal Diversity in the Intertidal Sediment of Chinese Seas Presents the Spatial Variation of Community Composition - Li, Wei; Wang, Mengmeng; Bian, Xiaomeng; Guo, Jiajia; Cai, Lei (Frontiers in Microbiology, 2016)
The intertidal region is one of the most dynamic environments in the biosphere, which potentially supports vast biodiversity. Fungi have been found to play important roles in marine ecosystems, e.g. as parasites or symbionts of plants and animals, and as decomposers of organic material. The fungal diversity in intertidal region, however, remains poorly understood. In this study, sediment samples from various intertidal habitats of Chinese seas were collected and investigated for determination of fungal community and spatial distribution. Through ribosomal RNA internal transcribed spacer-2 (ITS2) metabarcoding, a high-level fungal diversity was revealed, as represented by 6,013 OTUs that spanned six phyla, 23 classes, 84 orders and 526 genera. The presence of typical decomposers (e.g. Corollospora in Ascomycota and Lepiota in Basidiomycota) and pathogens (e.g. Olpidium in Chytriomycota, Actinomucor in Zygomycota and unidentified Rozellomycota spp.), and even mycorrhizal fungi (e.g. Glomus in Glomeromycota) indicated a complicated origin of intertidal fungi. Interestingly, a small proportion of sequences were classified to obligate marine fungi (e.g. Corollospora, Lignincola, Remispora, Sigmoidea). Our data also showed that the East China Sea significantly differed from other regions in terms of species richness and community composition, indicating a profound effect of the huge discharge of the Yangtze River. No difference in fungal communities was detected, however, among habitat types (i.e. aquaculture, dock, plant, river mouth and tourism). These observations raise further questions on adaptation of these members to environments and the ecological functions they probably perform.